Comparison of Preoperative Computed Tomography and Intraoperative Estimation in Predicting the Version of a Single‐Wedge Femoral Stem. Issue 11 (30th September 2022) - Sun, Jingyang; Zhang, Yanchao; Shen, Junmin; Zheng, Qingyuan; Li, Tiejian; Zhang, Bohan; Zhou, Yonggang; Zhang, Guoqiang
Abstract : Objective: Early prediction of stem version aids in optimization of combined version during total hip arthroplasty (THA). This study aimed to analyze the discrepancy between stem version and native femoral version measured by different methods, and to explore which method can better predict the stem version. Methods: We retrospectively reviewed 26 patients (39 hips) treated with robot‐assisted THA in our hospital between September 2019 and December 2019. A straight, single‐wedge, cementless stem (Accolade II) was used in all cases. Preoperative femoral version was measured at three levels on computerized tomography (CT) scan from the top to the middle level of femoral neck (Level 1 to Level 3). During THA, the version on cutting surface was measured prior to femoral broaching based on two reference lines: mid‐cortical line and T line (trochanteric fossa to the middle of medial cortex). After femoral broaching, stem version was measured based on the femoral neck trial using Mako system (Stryker). In the statistical analysis, the difference and absolute discrepancy between stem version and femoral version measured with various methods were examined using paired t‐test, and the relationship between stem version and various femoral versions were examined using correlation analysis. Results: Mean femoral neck version (Level 1) was 9.5° ± 2.6° (range, −16.8°‐42.5°), while mean stem version measured by Mako system was 19.9° ± 2.0° (range, −8.0°‐49.0°). Femoral version measured with each method showed a moderate correlation with stem version ( p  < 0.05). There was a significant difference between stem version and femoral version except at Level 3, with a mean difference of 0.8° ± 13.6° ( p  = 0.729). With regard to the intraoperative estimation, stem version significantly increased compared to the value based on mid‐cortical line, with a mean difference of 8.4° ± 13.1° ( p  < 0.001). However, the mean value of stem version was a little smaller than that of femoral version measured by reference to T line, but without statistical significance ( p  = 0.156). No postoperative dislocations occurred during the study period. No revision was required for any component. Conclusions: The middle level of femoral neck on CT scan and T line on cutting surface are better references to measure femoral version for predicting postoperative stem version. However, the relationship between stem version and predictive value was flexible. Therefore, further three‐dimensional studies of postoperative CT are needed to validate the press‐fit fixation and rotational freedom of the single‐wedge stem. Abstract : We analyzed the discrepancy between stem version and native femoral version measured by different methods and explored which method can better predict the stem version. Twenty‐six patients (39 hips) treated with robot‐assisted THA were included. Preoperative femoral version was measured at three levels on CT scan from the top to the middle level of femoral neck. During THA, the version on cutting surface was measured prior to femoral broaching based on two reference lines: mid‐cortical line and T line (trochanteric fossa to the middle of medial cortex). After femoral broaching, stem version was measured using Mako system. Finally, the middle level of femoral neck on CT scan and T line on cutting surface are better references to measure femoral version for predicting postoperative stem version. However, the relationship between stem version and predictive value was flexible.